Mechanical and Magnetic Properties of Double Layered Nanostructures of Tin and Zirconium Oxides Grown by Atomic Layer Deposition - Aile Tamm; Helle-Mai Piirsoo; Taivo Jõgiaas; Aivar Tarre; Joosep Link; Raivo Stern; Kaupo Kukli (Nanomaterials, 2021)
Double layered stacks of ZrO2 and SnO2 films, aiming at the synthesis of thin magnetic and elastic material layers, were grown by atomic layer deposition to thicknesses in the range of 20–25 nm at 300 °C from ZrCl4, SnI4, H2O, and O3 as precursors. The as-deposited nanostructures consisted of a metastable tetragonal polymorph of ZrO2, and a stable tetragonal phase of SnO2, with complementary minor reflections from the orthorhombic polymorph of SnO2. The hardness and elastic modulus of the stacks depended on the order of the constituent oxide films, reaching 15 and 171 GPa, respectively, in the case of top SnO2 layers. Nonlinear saturative magnetization could be induced in the stacks with coercive fields up to 130 Oe.